The Influence of ROE, EPS, and PER On Company's Share Price (Study on companies listed on JII70 in 2019- 2021) - Joni, Joni; Wijaya, Trisna; Jabar, Yahya Abdul (Dinar : Jurnal Ekonomi dan Keuangan Islam, 2023)
Stock price is one indicator of successful management of the company. The factors which effects the movement of price of a stock are internal factors and also external factors. The internal factors are commonly can be known as fundamentals, these internal factors are related to financial reports such as ROE, EPS, and PER. This study was conducted on purpose to help determining whether there is found such a significant influence between ROE, EPS, and PER toward prices of share. The approach method applied in this research is quantitative approach. The results for ROE show a value of significance of 0.000 α = 0.05, which can be claimed that there I found such a significant influence of ROE and stock prices. EPS shows a value of significance of 0.000 α = 0.05, it can be seen that there is a significant effect of EPS and stock prices. PER shows a significance value of 0.429 α = 0.05, it can be known that there is no found any effect of PER and stock prices. According to the F test result, it can be known that ROE, EPS, and also PER simultaneously influence the stock prices.